Pick-up of fluoroquinolones from the aqueous phase via magnetically propeled microrobots: kinetics, thermodynamics, and site energy distribution analysis - Yongzheng Tang; Wenpeng Jia; Mutai Bao; Mutai Bao; Shengyao Qiu; YongRui Pi; Chongfeng Liu; Jinchen Zhao (Frontiers in Marine Science, 2023)
Removing fluoroquinolones (FQs) in marine culture tailwater is crucial for the coastal marine environment. The application of a bacteria-based microrobot for FQ removal was discussed. Norfloxacin (NOR) and levofloxacin (LEV) had static maximum adsorption capacities of 114.8 and 49.4 mg/g, respectively, by a magnetic microrobot. The experimental results of NOR adsorption by a magnetic microrobot were well supported by the Langmuir isotherm and Elovich kinetic models. Both the Langmuir isotherm model and the pseudo-second-order kinetic model may be able to accurately represent the LEV adsorption process. The mass transfer mechanism of the NOR and LEV adsorptions was divided into two steps and described better using the intraparticle diffusion (IPD) model. The exothermic and spontaneity of the sorption process were demonstrated through the study of thermodynamics. The magnetic microrobot’s heterogeneous surface was validated by the examination of site energy distribution. Additionally, this study demonstrated that the majority of the NOR and LEV sorption took place at sites with energies over 4.25 and 17.36 kJ/mol, respectively, supporting the notion that NOR and LEV adsorption constitute physical–chemical processes. Based on the above results, a magnetic microrobot, as a new-style green bio-adsorbent, can potentially be used to remove NOR and LEV from the mariculture in an inexpensive and effective manner.